Influência da variabilidade ambiental marinha na captura da sardinha-verdadeira Sardinella brasiliensis (Steindachner, 1879) no Sul do Brasil - Mesquita, Sherida Ferreira Pinheiro de (2013)
Sardinella brasiliensis is a marine pelagic fish that belongs to a single fish stock confined at the Brazilian coast, occurs from Rio de Janeiro (22 ° S) to Santa Catarina (29 ° S) states in southern Brazil. Environmental variables influence on the biology of fishes in different ways. Here we investigate the influence of marine environmental variability on the Catch per Unit of Effort (CPUE) of S. brasiliensis in southern Brazil for 10 years. We tested the correlation of the peaks of oscillation of CPUE with variables such as the sea surface temperature (SST), chlorophyll concentration and the Southern Oscillation Index (SOI). CPUE data were obtained from Fisheries Statistics Bulletins, from the University of Vale do Itajai (UNIVALI). The SST data come from the NOAA Pathfinder project, the chlorophyll concentration (CC) from the NASA Giovanni database and the SOI from the Australian Bureau of Meteorology database. We divided the study area into four areas, confined at the southern coast of Brazil down to the 100 m isobath. We calculated the anomalies of sea surface temperature (SSTA). All time series were treated using linear interpolation for missing points, a 3-point moving average filter, then submitted to cross-correlation analysis and wavelet transform. We found that CPUE and SST are inversely correlated while CPUE and CC are directly correlated. There is an annual cycle of CC and biannual for SSTA. The wavelet transform CPUE shows a strong signal in the period of 16 months, all along the time series. In the years 2001 to 2002 and from 2003 to 2006, the period of 21 months is also important and strong. Knowing that the sardine adult stock follows the dynamics of the Brazil Coastal Current, we suggest greater stability of the current in terms of more positive SSTAs and CCs favoring higher spawns more successful and improve conditions for recruitment of S. brasiliensis adult stock to a year later.